The Effect of TiO2 Layers on the Surface Properties of Materials - Šulcová, Jana; Papučová, Iveta; Pagáčová, Jana; Dubec, Andrej; Feriancová, Andrea; Dedinský Peter Sukeľ, Maroš (Manufacturing Technology Journal, 2024)
One of the ways to improve or change the surface properties of materials is to apply thin layers. TiO2-based layers are used to protect surfaces against wear or atmospheric and thermal effects (anti-corrosion, anti-abrasive and anti-static layers). They are also used in optical coatings, on windows or glasses (anti-reflective, self-cleaning and conductive transparent layers), in healthcare and in households to ensure the cleanliness of surfaces. The work deals with the effect of TiO2 layers on the surface properties of selected substrates. The layers were prepared by the sol-gel method using the dip-coating technique on glass and stainless steel. The morphology and topography of the surfaces of the uncoated and coated substrates were evaluated by atomic force microscopy. Scanning electron microscopy was used to determine the layer thickness. The effect of TiO2 layers on the surface properties of materials was also evaluated using wetting angles, surface energy and its polar and dispersion components. Based on the results, especially the higher surface energy value, we can conclude that the TiO2 layer influenced the surface properties of the studied solid materials.
Keywords: Sol-gel method; TiO2 layers; Surface properties; Roughness